Genetic Structure of Aedes (Stegomyia) albopictus Populations in Russia - Elena V. Shaikevich; Ludmila Karan; Marina Fedorova (Tehran University of Medical Sciences, 2023)
Background: Aedes (Stegomyia) albopictus was found for the first time in 2011 on the Black Sea coast in Russia, and during 2011-2019, the species expanded over two climate zones Cfa and Csa. Methods: Here, we studied the sequence diversity of the mitochondrial cytochrome c oxidase I (COI) gene, 1317-1433bp in length. In total, 131 specimens of Ae. albopictus sampled from 21 locations in Russia and Abkhazia were examined. Results: Two of the six identified mitochondrial haplotypes were detected for the first time. Four COI haplotypes were shared by at least two studied local populations. The most prevalent H1 and H2 haplotypes dominated in all the sampled localities in the Cfa zone. The H3 haplotype was prevalent in the Csa zone. Other haplotypes were rare. Phylogenetic analyses, spatial isolation and limited gene flow revealed that the samples from the Csa zone differed significantly from those from the Cfa zone.